EFFECT OF SODIUM TUNGSTATE ON SOME PHYSIOLOGICAL PARAMETERS IN RATS EXPOSED TO OXIDATIVE STRESS INDUCED BY HYDROGEN PEROXIDE - Suha Abd Alkareem Rasheed (Mesopotamia Journal of Agriculture)
This study was conducted to determine the anti oxidant ability of sodium tungstate on some physiological aspects resulted from H2O2 – induced oxidative stress in the rat adult females. Twenty eight of adult albino rat females were randomly divided into 3 groups (8 /each) where the first group is control fed with normal diet and normal drinking water Ad libitum whereas the second group treated with H2O2 (1 %) via drinking water, the third group was also treated with H2O2 (1 %) in the same manner above in addition to daily oral gavaging with sodium tungstate solution (170 mg/ kg body weight) for 30 days. Results showed that tungstate administration for rat females led to a significant (P≤0.05) elevation in the means of total body weight, hemoglobin concentration, follicular stimulating hormone, leutinizing hormone and serum glutathione, also tungstate administration caused a significant (P≤0.05) decrease in granulocytes and serum malondialdehyde concentration with no effect on uterus weight. In conclusion, there is an antioxidant effect of sodium tungstate which can ameliorates some physiological and general aspects of the rat females undertaken to experimental oxidative stress.